Aviation subsidy policy and regional wellbeing: Important indicators from relevant stakeholders’ perspectives - Wu H; Lin Y-H; Ngo T; Tsui KWH (Elsevier Ltd on behalf of the World Conference on Transport Research Society, 2024)
A failure to adequately reconcile stakeholder interests and opinions can increase the probability of a failed aviation subsidy request or a loss of regional opportunity. This study, instead of arguing the importance and offering critiques of aviation subsidies, conducts a survey of stakeholders in New Zealand and Taiwan and uses fuzzy analytic hierarchy process to evaluate and prioritise key air transport activities and regional wellbeing indicators regarding the design and implementation of aviation subsidy policies in the early stage of the COVID-19 pandemic. The findings show that destination served, flight frequency, local business activities, medical treatment, and rapid hazard response were considered the key factors of aviation subsidies. Integrating economic and social wellbeing into subsidy policy design and implementation is highly necessary. The results provide useful insights for the development of aviation subsidy policies aimed at improving regional wellbeing in New Zealand and Taiwan during the post-COVID-19 era.